A Lousy Reason for Surgery Cancellations. (July 2016) - Walker, Christian; Sebastian, Roby; Krishna, Senthil; Tobias, Joseph D.
Cancellation of surgery has significant adverse impact on patients, health care providers, and their associated facilities. Although head lice infestation has not been shown to be associated with adverse surgical outcomes, it often prompts case cancellation by surgical and anesthesia personnel. The purpose of our study was to evaluate the extent and impact of surgery cancellations due to head lice infestation. In our study, a total of 9 patients were cancelled over a 3-year period. Although there is no direct evidence to show that head lice infestation poses a risk to surgical outcomes, the possibility of underlying secondary bacterial infection at the skin excoriation site is often the concern in these patients. This study offers the first investigation into the impact of head lice infections on operating room cancellations, which may prove to be a potential source of intervention to prevent cancellations.